Entropy production rate is maximized in non-contractile actomyosin - Daniel S. Seara (Nature Portfolio, 2018)
Myosin motors drive the actin cytoskeleton out-of-equilibrium, but the role of myosin-driven active stresses in the accumulation and dissipation of mechanical work is unclear. Here, the authors synthesize an actomyosin material and find that the rate of entropy production increases non-monotonically with increasing accumulation of active stresses.